Leadership Styles and their Influence on Ethical Behaviour in the Education of Healthcare Professionals - Karel Sládek (Theology and Philosophy of Education)
The Organisation and Management in Healthcare programme in the Czech Republic has been established in the faculties of health studies. As the most common follow-up master’s degree programme, it also includes subjects that educate non-medical healthcare professionals in leadership. Given the experience of healthcare professionals with a negative leadership function style, it is important to pay attention to the teaching of different leadership styles with their impact on ethical behaviour. The presented article will present two leadership styles, servant leadership and transformational leadership, with their impact on ethics and values. Education in these approaches can change the style of performing a leadership function, the climate, and satisfaction in the workplace, and last but not least, the quality of the care provided.